TIME AS THE DYNAMIC ASPECT OF THE CONTINUUM - Arnold, James (European Scientific Journal, ESJ, 2015)
The Minkowski diagram, by which the concept of spacetime has been graphically represented and interpreted, is shown to have a pre-relativistic flaw: It depicts the relative motion of a body moving in time as-if it is moving along with the observer’s clock, not as it is actually observed, according to its own proper time. An alternative diagram provides an accurate representation of relativistic relationships and enables heuristic insights into the nature of relativistic effects, and of time, light, and gravitation.